Mensuração da contribuição externa em relação à sustentabilidade dos bancos comerciais: uma proposta de indicador e análise de fatores influenciadores no Brasil - Inácio, Leticia da Silva (2025)
The banking sector plays a key role in promoting sustainable development. By acting as an intermediary, it can influence the pace and direction of this development. Through its products, it generates an external contribution on society and the environment. Measuring this contribution allows for improvements in banks' strategic decisions regarding the allocation of financial resources to each product and facilitates the demand for a stricter stance on sustainability by their stakeholders. Despite this relevance, studies related to this challenge are still incipient and incomplete. Sustainability indicators in the banking sector are not standardized and focus mainly on the bank's internal processes and operations, not on its external contribution. In addition, there is no consensus on the governance factors that can influence sustainability performance and what this influence is. In view of this, the present project aims to propose indicators for measuring the external contribution of commercial banks in relation to sustainability based on their sustainable products and to identify the governance factors that influence this performance in the Brazilian context. To this end, an exploratory qualitative approach was chosen using the methods of a systematic literature review, a content analysis and an in-depth interview. A quantitative approach was also applied with descriptive analysis, cluster analysis, Mann-Whitney test and Spearman correlation. In this way, it was possible to define the concept of a sustainable bank and its role, build and verify a model of indicators of the external contribution of sustainability for the banking sector and identify that factors such as age, capital, nationality, proportion of black people on the board and adherence to the Global Compact may be related to the sustainability performance of banks. Thus, it is possible to contribute in both academic and practical areas. The research contributes to filling the gap in indicators for measuring the sustainable external contribution of banking sector. It also carries out a performance assessment using a new external contribution indicator. Finally, it also stands out for its focus on Brazil, being one of the first to address this issue after the publication of the Anbima taxonomy on ESG funds.